"The world is upside down" – The Innsbruck Goggle Experiments of Theodor Erismann (1883–1961) and Ivo Kohler (1915–1985). (July 2017) - Sachse, Pierre; Beermann, Ursula; Martini, Markus; Maran, Thomas; Domeier, Markus; Furtner, Marco R.
Abstract: The "Innsbruck Goggle Experiments" on long-term wearing of reversing mirrors, prismatic and half prismatic goggles, and colored half goggles represent a milestone in research on adaptation (adapting to the introduced "disturbance") and after-effects (after removal of the "disturbance"). By means of these goggles it is, for example, possible to invert or distort the visual field (such as flipping top and bottom or left and right), as well as to observe how individuals learn to change the image back to vertical or recognize left and right. The Innsbruck Experiments gave decisive momentum to further international research on the ontogenetic development of perception, special perception, color perception, perceptual constancy, sensorimotor coordination, as well as to the development of theories. In the current paper, aside from presenting the history and results of selected studies, we will give an introduction to the life and work of the protagonists of these studies in Innsbruck, namely Theodor Erismann (1883–1961) and Ivo Kohler (1915–1985). Furthermore, we will propose ideas for future research on cognition and neuroscience.